The Effect of Utilizing Electronic Medical Record Data on Improving Patient Care Quality at Hospital X - Je-ann Budiman Mahalong; Prihartono Aksan Halim (International Journal of Psychology and Health Science, 2025)
The utilization of Electronic Medical Records (EMR) plays a central role in the digital transformation of healthcare services by improving efficiency, documentation accuracy, and evidence-based clinical decision-making. Although national policies such as the Indonesian Ministry of Health Regulation No. 24/2022 and the SATUSEHAT interoperability platform have accelerated EMR adoption, challenges remain, including limited infrastructure, workflow resistance, and uneven digital literacy among healthcare workers. This study aims to analyze differences in service quality indicators before and after EMR implementation at Hospital X, including registration waiting time, pharmacy waiting time, medication errors, SOAP completeness, and CDSS adoption. Using a quantitative pre–post comparison design and Mann-Whitney analysis, results show significant improvements across all indicators (p < 0.001). Registration and pharmacy waiting times decreased, medication errors declined, while SOAP completeness and CDSS usage increased markedly. All variables demonstrated large effect sizes (r = 0.587–0.924), indicating strong practical impacts of EMR implementation. These findings confirm that EMR contributes significantly to enhancing service efficiency, patient safety, and clinical documentation quality, providing valuable empirical evidence for strengthening digital health strategies in hospital settings.